PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, TERHADAP KINERJA DOSEN DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA UNIVERSITAS SATYA NEGARA INDONESIA (USNI) - Guston Sitorus (Jurnal Manajemen, 2018)
The objective of this research is to anlize and test the effect of organizational cultural, work enviroment, and job satisfaction on performance. Performance is assumed to be significantly effected by the organizational cultural, work enviroment, and job satisfaction that pertain in the organization. The causal study reported here aimed to examine the hypothesis. It was conducted through a survey in the Satya Negara Indonesia University a sample of 50 lecturer from the overall population of 50 lecturer employe. The data of each variable were collected separately by the respondens’ filling in a questionnaire. The path technique was applied to analyze the data wich had been previously treated with the aggressive and coorelation procedure. The result proved that the employee performance was directly effected by the organizational cultural, the work envoroment, and job satisfaction was in turn, directly effected by organizational cultural and work enviroment. The findings suggest that the variation of performance of the lecturer might have been effected by the organizational cultural, the work enviroment, and the job satisfaction in the organization. This further implies the need take the variables of organizational cultural, job satisfaction, and performance into the consideration in the strategic planning of the human resources development in the Satya Negara Indonesia University